Co-exposure of carbon nanotubes with lead affects the metabolism of the ghost shrimp Palaemon pandaliformis (Stimpson, 1871) - Keila Nazaré de Oliveira Araújo; Ana Lúzia de Souza Araújo; Marcelo Barbosa Henriques; Luiz Gustavo Ribeiro; Diego Stéfani Teodoro Martinez; Edison Barbieri (Next Research, 2026)

Abundance and seasonal association of seabirds with seabob shrimp trawling at Ilha Comprida, São Paulo, Brazil - Allan Clé Porto; Edison Barbieri (Ornithology Research, 2026)
This article examines the interactions between seabob shrimp trawling and six seabird species in Ilha Comprida, São Paulo, Brazil. The species studied include the brown booby, magnificent frigatebird, Cabot’s tern, royal tern, kelp gull, and Neotropic cormorant. Observations were conducted along a 70 km beach transect, with a width of 300 m from the waterline, by driving at an average speed of 20 km/h. The Pearson correlation coefficient was used to assess the relationship between seabird abundance and the number of shrimp fishing boats. The magnificent frigatebird showed a strong correlation, with the highest abundance within the first 20 km of the southernmost region, particularly between September and February, aligning with peak fishing season. The royal tern exhibited a moderate correlation, with consistent abundance up to kilometer 35 and peak concentrations within the first 5 km. Kelp gulls had a weaker correlation, with the greatest sightings within the first 40 km, predominantly from June to February. Brown boobies demonstrated a moderate correlation, with increased abundance starting from the 13th boat, primarily distributed within the first 20 km, peaking in September. The Neotropic cormorant had a very weak correlation, showing a uniform distribution mainly within the first 15 km, with presence during spring-summer, from August to February. This study highlights the spatial and temporal relationships between shrimp trawling activities and seabird distribution, emphasizing the varying degrees of dependency of each species on fishing activities.

Occurrence of the Non-Native Species Macrobrachium rosenbergii (De Man, 1879) in Brazilian Protected Areas: Ecological Risks and the Urgency of Monitoring - Edison Barbieri; André Luiz Matins Villar; Erick Paiva Barbieri; Ernesto Brugnoli Oliveira; Ítalo Braga Castro (Estuaries and Coasts, 2026)
The occurrence of the non-native species Macrobrachium rosenbergii has been recorded in multiple drainage basins and estuarine systems throughout Brazil, including 11 coastal Protected Areas. In the Cananéia estuarine–lagoon complex, participatory monitoring conducted between 2015 and 2025 revealed persistent populations and the presence of ovigerous females, indicating local establishment and reproduction. The species exhibits broad tolerance to salinity gradients and marked trophic plasticity, allowing its integration into native ecological networks. Records are concentrated in the Southeast and Northeast regions and are closely associated with aquaculture areas. The presence of this invasive crustacean in sensitive estuarine ecosystems, such as the Atlantic Forest Biosphere Reserve, represents a serious threat to native biodiversity by intensifying competitive interactions, altering trophic dynamics, and increasing sanitary risks, thereby requiring urgent monitoring and management actions.

Economics of small-scale urban aquaponics in Brazil: a case study on Astyanax lacustris and Lactuca sativa - Edison Barbieri; Leonardo Castilho-Barros; Gabriele Drigo Galan; Milton Ricardo Azedo; Marcelo Barbosa Henriques (Aquaculture International, 2025)

Arsenic bioaccumulation in ready-to-eat oysters can contribute to the selection of WHO critical priority Enterobacterales displaying a virulent behavior - Felipe Vásquez-Ponce; Nicolas Gamboa-Acuña; Aline Pereira de Oliveira; Johana Becerra; Jesus G.M. Pariona; Leon de Oliveira Lima; Aline de Carvalho Elias; Maciel Santos Luz; Mateus Rocha Ribas; Gustavo Rocha; Fernanda Esposito; Patricio Muñoz; et al. (Food Research International, 2025)

Assessing the anthropogenic disturbance impact on migratory and resident shorebirds in sandy beaches of the São Paulo, Brazil Coast - Karina Anahí Ávila Esparza; Bruno Lima; Edison Barbieri (Ornithology Research, 2025)

Green mussel Perna viridis (L.) on the Brazilian coast: a fast-spreading invasive species reaching protected areas - Edison Barbieri; Ítalo Braga Castro; Daniel Caracanhas Cavallari; Rodrigo Cesar Marques; Ernesto Brugnoli Olivera (Marine Biology, 2025)

A review of dietary approaches for ammonia toxicity remediation in fish - Seyyed Morteza Hoseini; Edison Barbieri; Baki Aydın; Morteza Yousefi (Aquaculture International, 2024)

Norovirus GII and astrovirus in shellfish from a mangrove region in Cananéia, Brazil: molecular detection and characterization - Andrea Vasquez-García; Julian Eduardo Mejia-Ballesteros; Silvia Helena Seraphin de Godoy; Edison Barbieri; Ricardo Luiz Moro de Sousa; Andrezza Maria Fernandes (Brazilian Journal of Microbiology, 2022)

Carbofuran affects behavior and metabolism of the Atlantic Forest lambari Deuterodon iguape, a native species from Brazil - Ricardo Claudionor Mendes; Marcelo Barbosa Henriques; Edison Barbieri (Environmental Science and Pollution Research, 2021)

Sublethal effects of propiconazole on the metabolism of lambari Deuterodon iguape (Eigenmann 1907), a native species from Brazil - Marcelo Barbosa Henriques; Karina Fernandes Oliveira Rezende; Leonardo Castilho-Barros; Edison Barbieri (Fish Physiology and Biochemistry, 2021)

Effects of multiwalled carbon nanotubes and carbofuran on metabolism in Astyanax ribeirae, a native species - Edison Barbieri; Alessandra Maria Tegon Ferrarini; Karina Fernandes Oliveira Rezende; Diego Stéfani Teodoro Martinez; Oswaldo Luiz Alves (Fish Physiology and Biochemistry, 2019)

Lambari fish Deuterodon iguape as an alternative to live bait for estuarine recreational fishing - Marcelo Barbosa Henriques; Lúcio Fagundes; Maria Letizia Petesse; Newton José Rodrigues da Silva; Karina Fernandes Oliveira Rezende; Edison Barbieri (Fisheries Management and Ecology, 2018)
Fishing tourism is growing steadily in Brazil. Artisanal fishers meeting the demand for recreational fishing are capturing live juvenile shrimp in the estuaries and selling them for live bait, preventing the recruitment of a larger contingent into the ocean. This study compares the efficiency of using lambari, Deuterodon iguape Eigenmann, as live bait with the shrimp, Penaeus schmitti Burkenroad , while fishing for common snook ( Centropomus spp.), as well as to evaluate the swimming behaviour of D. iguape in different salinities. The results showed that there was no significant difference between the live baits used ( P. schmitti vs D. iguape ). The month, the period of the day and salinity presented differences. The size of the species did not depend on the type of bait used. There was no statistical difference in swimming behaviour, but there was a trend of increased speed and displacement in the group exposed to a salinity of 10 g/L. In conclusion, D. iguape appears as effective as P. schmitti and can be successfully used as live bait; and from an ecological point of view, it reduces the impact of fishing on juvenile shrimp.

Acute toxicity of ammonia on juvenile cobia (Rachycentron canadum, Linnaeus, 1766) according to the salinity - Edison Barbieri; Sonia Assami Doi (Aquaculture International, 2012)

Assessment of trace metal concentration in feathers of seabird (Larus dominicanus) sampled in the Florianópolis, SC, Brazilian coast - Edison Barbieri; Elisangela de Andrade Passos; Alexandre Filippini; Izaias Souza dos Santos; Carlos Alexandre Borges Garcia (Environmental Monitoring and Assessment, 2010)

Effects of zinc and cadmium on oxygen consumption and ammonium excretion in pink shrimp (Farfantepenaeus paulensis, Pérez-Farfante, 1967, Crustacea) - Edison Barbieri (Ecotoxicology, 2009)

Effect of 2,4-D herbicide (2,4-dichlorophenoxyacetic acid) on oxygen consumption and ammonium excretion of juveniles of Geophagus brasiliensis (Quoy & Gaimard, 1824) (Osteichthyes, Cichlidae) - Edison Barbieri (Ecotoxicology, 2009)